Frameworks, models and theories for prevention of child maltreatment: protocol for a scoping review from a population health perspective - Juan Victor Ariel Franco; Freia De Bock; Adrienne Alayli; Lena Rasch; Christian Ballmeyer (BMJ Open)
Introduction Child maltreatment (CM) is a major public health issue with lifelong consequences on mental health, quality of life, educational and economic prospects of children who experienced CM. Early identification of maltreated children is important to prevent further CM and ensure that children’s basic needs are met, as well as to address and avoid further consequences. However, above and beyond early identification, it is crucial to avoid the occurrence of CM. This may include the reduction of risk factors at the family and community level as well as creating supportive environments for growing up safely. Therefore, we need to understand the prevention of CM conceptually and view it not only from a medical perspective, but also from a population health perspective. The aim of this scoping review is to identify and describe theories, models or frameworks on the prevention of CM from a broad population health perspective, considering primary, secondary and tertiary prevention strategies.Methods and analysis A broad search in four databases (PubMed (NIH NLM), PsycInfo (Ovid), CINAHL Plus (EBSCOhost) and Web of Science (Clarivate)) will be conducted from 2009 to current. Additionally, the grey literature on websites from key public health organisations will be considered. Results will be reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews: Checklist and Explanation (2018). The review will include articles describing a theory, model or framework on prevention strategies for CM. Studies focussing on single interventions that do not describe prevention strategies conceptually, will be excluded. General characteristics of the frameworks, theories and models and information on types of prevention strategies they describe will be extracted. Findings will be presented in a structured table format as well as narratively.Ethics and dissemination As we will not collect any personal, confidential or sensitive data, ethical approval is not required. We will publish our results in a scientific journal, present them at conferences and use them for further knowledge translation activities. The scoping review is registered with the Open Science framework: https://osf.io/49g7z/.